An update on the role of gut microbiota in chronic inflammatory diseases, and potential therapeutic targets. (3rd October 2018) - Laing, Bobbi; Barnett, Matthew P. G.; Marlow, Gareth; Nasef, Noha Ahmed; Ferguson, Lynnette R.
ABSTRACT: Introduction : The human microbiome plays a critical role in human health, having metabolic, protective, and trophic functions, depending upon its' exact composition. This composition is affected by a number of factors, including the genetic background of the individual, early life factors (including method of birth, length of breastfeeding) and nature of the diet and other environmental exposures (including cigarette smoking) and general life habits. It plays a key role in the control of inflammation, and in turn, its' composition is significantly influenced by inflammation. Areas covered : We consider metabolic, protective, and trophic functions of the microbiome and influences through the lifespan from post-partum effects, to diet later in life in healthy older adults, the effects of aging on both its' composition, and influence on health and potential therapeutic targets that may have anti-inflammatory effects. Expert commentary : The future will see the growth of more effective therapies targeting the microbiome particularly with respect to the use of specific nutrients and diets personalized to the individual.